Synthesis and properties of a biodegradable polymer-drug conjugate: Methotrexate-poly(glycerol adipate) - Suksiriworapong, Jiraphong; Taresco, Vincenzo; Ivanov, Delyan P.; Styliari, Ioanna D.; Sakchaisri, Krisada; Junyaprasert, Varaporn Buraphacheep; Garnett, Martin C. (Elsevier, 2018)
Polymer-drug conjugates have been actively developed as potential anticancer drug delivery systems. In this study, we report the first polymer-anticancer drug conjugate with poly(glycerol adipate) (PGA) through the successful conjugation of methotrexate (MTX). MTX-PGA conjugates were controllably and simply fabricated by carbodiimide-mediated coupling reaction with various high molar ratios of MTX. The MTX-PGA conjugate self-assembled into nanoparticles with size dependent on the amount of conjugated MTX and the pH of medium. Change in particle size was attributed to steric hindrance and bulkiness inside the nanoparticle core and dissociation of free functional groups of the drug. The MTX-PGA nanoparticles were physically stable in media with pH range of 5–9 and ionic strength of up to 0.15 M NaCl and further chemically stable against hydrolysis in pH 7.4 medium over 30 days but enzymatically degradable to release unchanged free drug. Although 30%MTX-PGA nanoparticles exhibited only slightly less potency than free MTX in 791T cells in contrast to previously reported human serum albumin-MTX conjugates which had >300 times lower potency than free MTX. However, the MTX nanoparticles showed 7 times higher toxicity to Saos-2 cells than MTX. Together with the enzymic degradation experiments, these results suggest that with a suitable biodegradable polymer a linker moiety is not a necessary component. These easily synthesised PGA drug conjugates lacking a linker moiety could therefore be an effective new pathway for development of polymer drug conjugates.